Underage Murder Case Against Robbers in the Perspective of Criminal Law and Islamic Criminal Law - M. Junaidi; Tanuhita Kumara Putri Azalia Sukoco (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
This research explores legal issues related to perpetrators of child abuse with a focus on the analysis of the decision of the Kepanjen District Court (Number: 1/Pid.Sus-Anak/2020/PN.KPn). The crime of abuse, which involves an attack on another individual with the aim of torturing or oppressing, has serious implications in criminal law and Islamic criminal law. The research uses a statutory and case approach, exploring normative and doctrinal aspects of Indonesian and Islamic law that are relevant to the case. The main data is obtained from primary legal materials such as the 1945 Constitution, Criminal Code, Law Number 11 of 2012, Law Number 35 of 2014 concerning Child Protection, as well as Islamic legal sources such as the Qur'an and Hadith and also secondary legal materials such as books, articles, journals, and other scientific works. By using deductive analysis, this research aims to provide an overview and solution to legal problems that occur, especially regarding legal protection for minors who commit persecution as a form of defense that causes the death of begal both according to criminal law and Islamic law. This study found that children who commit persecution against begal until they die, both criminal law and Islamic law both agree that minors can only be sentenced as a last resort and must still pay attention to the best interests of the child. In juvenile law, research considers psychological factors, the need for compassion, and rehabilitation efforts to achieve balanced justice. This research contributes to the understanding of criminal law and Islamic criminal law related to cases of sexual abuse, especially those involving underage offenders.